Otoneurologic Findings in a Fishermen Population of the State of Santa Catarina: Preliminary Study - Zeigelboim,Bianca Simone (2014)
Introduction  Fishing, one of the oldest productive activities, is an important sector of the national and world economy. Aim  To evaluate the vestibular behavior in a population of fishermen. Methods  In a retrospective and cross-sectional study, 13 fishermen (mean 45.0), between 33 and 62 years of age, were submitted to anamnesis, otorhinolaryngological evaluation, and vestibular exam through the vector electronystagmography. Results  The most evident otoneurologic symptoms were hearing loss (76.9%), tinnitus (61.7%), dizziness (46.1%), and headache (46.1%). The most evident clinical symptoms were fatigue (46.1%), depression (23.0%), anxiety (15.3%), insomnia (7.7%), and agitation during sleep (7.7%). There were alterations in the vestibular exam in 5 fishermen (38.5%) discovered in the caloric test. There was a prevalence of alteration in the peripheral vestibular system. There was a major frequency of the peripheral vestibular irritative syndrome. Conclusion  The otoneurologic complaints were frequent in the population studied to verify the importance of allowing labyrinth exams and the need for adopting preventive measures relating to noise exposure as well as carbon monoxide exposure, because they can cause and/or enhance various manifestations of labyrinthine vestibular impairment that can affect the quality of life of these workers.